ATP citrate lyase is increased in human breast cancer, depletion of which promotes apoptosis - Diyu Wang; Lei Yin; Jinrong Wei; Zhixue Yang; Guoqin Jiang (Tumor Biology, 2017)
Breast cancer is a malignant tumor that is harmful to women’s health around the world. Investigating the biological mechanism is, therefore, of pivotal importance to improve patients’ prognoses. Compared to non-neoplastic tissues, enhanced glucose and lipid metabolism is one of the most common properties of malignant breast cancer. Adenosine triphosphate (ATP) citrate lyase is a key enzyme linking aerobic glycolysis and fatty acid synthesis and is of high biological and prognostic significance in breast cancer. In our clinical study, fresh clinical tissues were used to analyze ATP citrate lyase expression by western blotting, and paraffin archived samples from 62 breast cancer patients were used to analyze ATP citrate lyase expression by immunohistochemistry. In the cellular study, following small interfering RNA–mediated inhibition of ATP citrate lyase in MCF-7 cells, cell viability and apoptosis were measured using the Cell Counting Kit-8 and flow cytometry, respectively. Breast cancer tissues showed strong expression of ATP citrate lyase, whereas adjacent normal tissues showed weak expression. Silencing of endogenous ATP citrate lyase expression by small interfering RNA in MCF-7 cells suppressed cell viability and increased cell apoptosis. Collectively, our study revealed that expression of ATP citrate lyase was significantly increased in breast cancer tissue compared with normal tissue. In addition, we found that depletion of ATP citrate lyase suppressed tumor growth, which suggests that ATP citrate lyase–related inhibitors might be potential therapeutic approaches for breast cancer.